2018
DOI: 10.1111/ijfs.13944
|View full text |Cite
|
Sign up to set email alerts
|

In‐line estimation of the elastic module of milk gels with variation of temperature protein concentration

Abstract: Summary The cutting time of the curd is a relevant factor to improve the quality of the cheese. Only a few studies have focused on the prediction of objective rheological parameters, such as the elastic modulus of the gel (G′) instead of a subjective cut‐off time. A complete randomized factorial design with three replicates was used to determine the effect of proteins and temperature in the prediction of G′ values, gelation time and cutting time in reconstituted skimmed milk gels. The coagulation process was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
4
4
0
Order By: Relevance
“…At that moment, all three gels were visually ready to be cut, although the rheological measurements showed significantly different G' values: 19.9 ± 1.71 Pa (Gc), 11.9 ± 1.96 Pa (G8) and 7.3 ± 1.46 Pa (G9). Taking into account the different rheometers used in the mentioned studies, the storage moduli of Gc were comparable to the values reported for pasteurized cow milk by Guinee, Pudja and Mulholland [25] and Yu, et al [28], but lower than the ones reported by Salvador, Arango and Castillo [26] and Panthi, Kelly, Sheehan, Bulbul, Vollmer and McMahon [3]. However, the other two G' values (for G8 and G9) were much higher than the G' of cow milk heated to 80 °C/20 min [28] indicating the The shapes of the three presented curves were notably different.…”
Section: Rheological Measurementssupporting
confidence: 82%
See 1 more Smart Citation
“…At that moment, all three gels were visually ready to be cut, although the rheological measurements showed significantly different G' values: 19.9 ± 1.71 Pa (Gc), 11.9 ± 1.96 Pa (G8) and 7.3 ± 1.46 Pa (G9). Taking into account the different rheometers used in the mentioned studies, the storage moduli of Gc were comparable to the values reported for pasteurized cow milk by Guinee, Pudja and Mulholland [25] and Yu, et al [28], but lower than the ones reported by Salvador, Arango and Castillo [26] and Panthi, Kelly, Sheehan, Bulbul, Vollmer and McMahon [3]. However, the other two G' values (for G8 and G9) were much higher than the G' of cow milk heated to 80 °C/20 min [28] indicating the The shapes of the three presented curves were notably different.…”
Section: Rheological Measurementssupporting
confidence: 82%
“…Based on the rheolological measurements, Guinee, et al [25] suggested the fixed storage modulus G' = 16 Pa as being the proper cutting time stiffness of gel. According to Salvador, et al [26], the value of the cutting time gel stiffness is G' = 30 Pa. Recently, Panthi, Kelly, Sheehan, Bulbul, Vollmer and McMahon [3] established the term cutting window as the time in which the value of G' lies between 35 and 70 Pa, when the gel is ready to be cut.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…2 and 3). High values in DR are related to shorter coagulation times, as previous studies have shown (Arango et al, 2018a;Salvador et al, 2019). DR increases at high protein levels but decreases as the fat concentration increases for the two probes evaluated (Fig.…”
Section: Multi Ber Probe Selectionsupporting
confidence: 62%
“…As seen above, the controversy raised by the separation of the non-enzymatic phase of milk coagulation into phases of aggregation and hardening will serve as the basis for studying, in a first approach, the different models that describe the phenomenon of micellar aggregation. Payne and Castillo [9], who studied milk coagulation using an NIR light scattering sensor, described in the sigmoidal curve generated by the instrument response two periods that overlap during coagulation (Figure 2): (A) the period corresponding to the phase of enzymatic hydrolysis of micellar destabilization, which goes from the addition of the enzyme to approximately the inflection point of the light scattering ratio (R) or time corresponding to the maximum of the first derivative of R (tmax); and (B) the period corresponding to the non-enzymatic phase of coagulation which consists of two phases: (a) the period corresponding to the aggregation phase of the destabilized micelles that goes from tmax until the moment in which the gel begins to offer mechanical resistance (e.g., the point that could be identified, approximately, as the time at which a value of G' = 1 Pa is reached, determined by a rheometer [10,11], related to t2min2 [12]) and (b) the asymptotic period corresponding to the hardening phase of the casein gel that continues until the optimum curd cutting point is reached. Harboe et al [13] and Fox et al [8] also describe differences between the aggregation phase and the hardening phase, but from the point of view of changes in viscosity and rheological parameters.…”
Section: Introductionmentioning
confidence: 99%